PERCONTOHAN BUDIDAYA KEDELAI HITAM DI LAHAN SAWAH DESA KEMUMU DAN OLAHAN HASILNYA - Murcitro, Bambang Gonggo; Pujiwati, Hesti; Tutuarima, Tuti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2021)
This devotional activity aims to improve farmers' skills in the cultivation of black soybeans and increase the selling value of black soybeans which can ultimately increase farmers' incomes in Kemumu Village. Devotional activities are designed in 3 types of activities that are mutually sustainable, namely (1) education and extension of black soybeans, (2) the manufacture of black soybean planting experiments, and (3) training and the making of black soybean processing. The results of the activity showed that the education and counseling carried out by the devotional team was able to increase knowledge about black soybeans both planting techniques and processing of seed products. Cultivation of soybean plants and the manufacture of processed soybean seeds into tempe, tofu, and soy sauce have been successfully carried out by the farmer's group of Kemumu Village, North Bengkulu. The result achieved by the black soybean variety Detam 4 is 1.39 tons/ha. To follow up on this activity, the proposed suggestions include: (1) in the future members of the target farming group are expected to continue to carry out the practice of cultivating black soybeans on a wider scale (2) members of the target farming group to keep making tempe and soybeans on an industrial scale to increase household income, (3) to the government to provide a channel of funds to meet adequate equipment resources in the production of tofu and industrial-scale tempe.